Conditionality of individual and team technicaly-tactic women basketball player functions on the level of situationaly- motor readiness - Basinac, I.; Mikic, B.; Dautbasic, S. (Acta Kinesiologica, 2008)
The research was conducted on 43 female basketball players from 6 clubs of First division basketball women competition in Bosnia and Herzegovina. The main goal of this research is by using methodologically analytical methods obtaining appropriate effective procedure to consider conditionality of individual and team technically-tactic functions on the level and character of situational motor readiness. For that reason our major issue was outlining methodology of differentiated approach to identify belonging of women basketball players to specific type groups according to structure affinity of their situational-motor skills, which was presented by hierarchical cluster analysis. To research indicators that could be the main criteria to measure effectiveness of rival activity of tested women basketball players, multiple analysis of variance of tactics quality was used to identify rational group of dominant components and it`s reducing to optimal measure.